Different patterns in root and soil fungal diversity drive plant productivity of the desert truffle Terfezia claveryi in plantation. (3rd August 2021) - Arenas, Francisco; Navarro‐Ródenas, Alfonso; Marqués‐Gálvez, José Eduardo; Ghignone, Stefano; Mello, Antonietta; Morte, Asunción
Summary: The desert truffle Terfezia claveryi is one of the few mycorrhizal fungi currently in cultivation in semiarid and arid areas. Agroclimatic parameters seem to affect its annual yield, but there is no information on the influence of biotic factors. In this study, fungal diversity was analysed by high‐throughput sequencing of the ITS2 rDNA region from soil and root samples to compare productive and non‐productive mycorrhizal plants in a 4‐years old plantation (Murcia, Spain). The fungal metaprofile was dominated by Ascomycota phylum. Desert truffle productivity was driven by different patterns of fungal species composition in soil (species replacement) and root (species richness differences). Moreover, positive associations for ectomycorrhizal and negative for arbuscular mycorrhizal guilds were found in productive roots, and positive associations for fungal parasite‐plant pathogen guild in non‐productive ones. Soil samples were dominated by pathotroph and saprotroph trophic modes, showing positive associations for Aureobasidium pullulans and Alternaria sp. in productive areas, and positive associations for Fusarium sp. and Mortierella sp. were found in non‐productive soils. Finally, some significant OTUs were identified and associated to ascocarp producing patches, which could serve as predictive and location markers of desert truffle production.